Learning Environment Design for Education Formulation the Future - Taufiqqurrahman, Taufiqqurrahman; Kuswandi, Dedi; Setyosari, Punaji; Ulfa, Saida (Lembaga Penelitian dan Pendidikan Mandala, 2023)
A survey conducted by Deloitte's recently (in 2023) found data that